Electrochemical Reducion of Pyridine-2- Carbakdegtde at Stainless Steel Cathode in basic Aqueous Ethanol Medium: Investigation of Electrochemical Reduction of Pyridine-2-Carbakdegtde for 1,2-Glycol Preparation (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The electrochemical reduction of the Pyridine-2-Carbakdegtde was carried out at the controlledpotential in l M acetate buffer at pH 9 for the purpose of investigating this type of reduction as a possiblesynthetic procedure for the preparation of 1, 2-glycols. The products formed during electrolysis atconstant cathode potential are reported here.